INICIATION TO THE ENGLISH LANGUAGE IN THE PRESCHOOL: PEDAGOGIC IMPLICATIONS OF THE HISTORICAL CULTURAL THEORY - Brandao, Silvane Maria Pereira; Lima, Elieuza Aparecida de [UNESP]; Valiengo, Amanda (Centro Univ Nove Julho, 2023)
Given the current situation of insertion of the English language since preschool, this study has perspectives of critically reflecting on the elements that underlie an education that promotes favorable conditions for the maximum development of children's intelligence and personality. This is a bibliographic research focused on questions about the initiation to the English language in classes of young children, with the general objective of systematizing some of the possible pedagogical implications arising from Historical-Cultural Theory for reflections on initiation to the English language in preschool age. The research is based on Leontiev (2001), Vygotsky (2001), Davydov (1988) and Repkin (2003), to discuss concepts of human being, learning, appropriation, objectification, mediation, language and human development, considering them principles capable of guiding the achievement of a humanizing education. The bibliographic investigation aims deepening in authors dedicated to the initiation of English language and also in studies arising from the Historical-Cultural Theory for the systematization of some pedagogical implications of this theoretical framework essential to the initiation to the English language in the preschool age. The results found refer to the possibility of promoting human development through an initiation into the English language guided by the appreciation of the characteristics and needs of childhood and by the activity of the child.
Keywords: historical-cultural theory; humanization; initiation to the english language; language; preschool education